Innovative Approaches for Improving ORC Performance: A Review of Pure Fluids, Zeotropic Mixtures, and Nanoparticles - Kumi, Ebenezer; Veeredhi, Vasudeva Rao; Enweremadu, Christopher (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Although the organic Rankine Cycle (ORC) is said to effectively capture low-grade heat, its commercialization has been limited because of working fluid constraints and inefficiencies resulting from operating at low temperatures. This study reviews the working fluids used in organic Rankine cycles and examines how nanoparticles could enhance the efficiency of the ORC, by enhancing the thermophysical properties of the working fluids. Results from this review showed that zeotropic mixtures of pure fluids, provide a viable approach to improving the thermophysical characteristics of organic working fluids and have the potential to achieve thermo-economic performance superior to that of individual pure fluids. Research results on the relative effectiveness of zeotropic mixtures and pure fluids, however, are conflicting and call for further study. Although nanofluids have shown potential as heat transfer fluids, there has not been much research done on them as organic Rankine cycle working fluids. In comparison to typical nanoparticles, metal-organic heat carriers have been recognized as having substantial potential to improve organic Rankine cycle thermodynamic efficiency. Future study on nanofluids, particularly in zeotropic mixtures, is crucial for the creation of new working fluids for developing ORCs that could achieve a balance between thermodynamic, economic, and environmental performance required to recover low-grade heat and the generation of electricity.